RANCANG BANGUN PROTOTYPE PLTMH DENGAN TURBIN TURGO - Aditya Kresna Artha K, I Gede Putu; Arta Wijaya, I Wayan; Janardana, I Gusti Ngurah (Jurnal SPEKTRUM; Vol 9 No 2 (2022): Jurnal SPEKTRUM, 2022)
Learning about using water resources as a MHP is need to implemented for Electrical Engineering students at Udayana University. Currently at the Energy Conversion Laboratory the Electrical Engineering Study Program Faculty of Engineering Udayana University cannot yet to carry out practicum on MHP due to the unavailability of devices and equipment. Therefor it needs to analyze the design of this MHP prototype. Turgo turbine is a classification of impulse turbine that require water pressure as a source to rotate the turbine. In this research a prototype of MHP with a turgo turbine has been formed which has a total of 18 blades with blade length 6,8 cm, blade width 4,68 cm, and blade depth 1,17 cm. This prototype has 1 nozzle with a diameter 2 cm that has beam angle of 70° which emits water with a pressure of 21 psi. This prototype is capable of producing power 7,268 Watt and torque 0,1228 Nm so that this prototype efficiency is 1,099%.